Identification and characterization of natural antibodies against tau protein in an intravenous immunoglobulin product - Hromadkova, Lenka; Kolarova, Michala; Jankovicova, Barbora; Bartos, Ales; Ricny, Jan; Bilkova, Zuzana; Ripova, Daniela (Journal of neuroimmunology, 2015)
The latest therapeutic approaches to Alzheimer disease are using intravenous immunoglobulin (IVIG) products. Therefore, the detailed characterization of target-specific antibodies naturally occurring in IVIG products is beneficial. We have focused on characterization of antibodies isolated against tau protein, a biomarker of Alzheimer's disease, from Flebogamma IVIG product. The analysis of IgG subclass distribution indicated skewing toward IgG3 in anti-tau-enriched IgG fraction. The evaluation of their reactivity and avidity with several recombinant tau forms was performed by ELISA and blotting techniques. Truncated non-phosphorylated tau protein (amino acids 155-421) demonstrated the highest reactivity and avidity index. We provide the first detailed insight into the reactivity of isolated natural antibodies against tau protein.
Keywords: imunosorpční techniky; Epitopes; Humans; imunoglobulin G; Protein Binding; molekulová hmotnost; Immunoglobulins, Intravenous; Immunosorbent Techniques; tau Proteins; Immunoreactivity; Natural antibodies; lidé; peptidy; proteiny tau; Peptides; Alzheimer disease; vazba proteinů; Intravenous immunoglobulins; Avidity; Tau protein; intravenózní imunoglobuliny; epitopy; terciární struktura proteinů; Immunoglobulin G; Protein Structure, Tertiary; Molecular Weight